2005
DOI: 10.1161/01.res.0000171901.40952.0d
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Shear Stress–Related Gene Expression After Experimentally Altered Venous Return in the Chicken Embryo

Abstract: Abstract-Hemodynamics play an important role in cardiovascular development, and changes in blood flow can cause congenital heart malformations. The endothelium and endocardium are subjected to mechanical forces, of which fluid shear stress is correlated to blood flow velocity. The shear stress responsive genes lung Krüppel-like factor (KLF2), endothelin-1 (ET-1), and endothelial nitric oxide synthase (NOS-3) display specific expression patterns in vivo during chicken cardiovascular development. Nonoverlapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
162
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(175 citation statements)
references
References 41 publications
11
162
1
1
Order By: Relevance
“…We showed that already during embryonic development, patterning of KLF2 gene expression relates to areas of high shear stress (Groenendijk et al, 2004;Vennemann et al, 2006). Experimental changes in embryonic blood flow lead to changes in gene expression patterning of KLF2, ET1, and eNOS (Groenendijk et al, 2005), and lead to loss of proper cardiovascular function (Stekelenburg-de Vos et al, 2005Ursem et al, 2004) and the development of structural anomalies (Hogers et al, 1997(Hogers et al, , 1999. We have recently identified the inverse correlation between the expression of KLF2 and the presence of endothelial primary cilia in the embryonic heart (Van der Heiden et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that already during embryonic development, patterning of KLF2 gene expression relates to areas of high shear stress (Groenendijk et al, 2004;Vennemann et al, 2006). Experimental changes in embryonic blood flow lead to changes in gene expression patterning of KLF2, ET1, and eNOS (Groenendijk et al, 2005), and lead to loss of proper cardiovascular function (Stekelenburg-de Vos et al, 2005Ursem et al, 2004) and the development of structural anomalies (Hogers et al, 1997(Hogers et al, , 1999. We have recently identified the inverse correlation between the expression of KLF2 and the presence of endothelial primary cilia in the embryonic heart (Van der Heiden et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This regulation apparently aims to level off shear stress, through activation or repression of vasoactive genes like endothelial nitric oxide synthase (eNOS, NOS3) or endothelin-1 (ET1), and modulate the activation state of the cells. In this respect, the zinc finger transcription factor Krü ppel-like factor-2 (KLF2/LKLF) plays a central role, in vitro (SenBanerjee et al, 2004), as well as in vivo in the adult (Lee et al, 2006;Dekker et al, 2005Dekker et al, , 2006 and embryonic vasculature (Groenendijk et al, 2004(Groenendijk et al, , 2005. KLF2 is expressed in areas of high and steady or pulsatile flow where it positively regulates eNOS and downregulates ET1, whereas prolonged oscillatory flow suppresses KLF2 expression (Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Photographic images, even with scales, do not have the capacity to measure depth, limiting their utility for three-dimensional (3D) quantification. The 3D serial reconstruction using histological sections has dramatically improved understanding of heart development with the ability to combine geometry and the expressions of cell and/or matrix proteins (Moorman et al, 2000;Groenendijk et al, 2005). However, accuracy of this process is extremely sensitive to the number of sections processed, limiting its use to research labs with specifically dedicated technicians and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the necessity of adequate endothelial signaling, venous clipping eventually results in a spectrum of cardiac malformations, including including atrioventricular (AV) and outflow tract (OFT) anomalies (Hogers et al, 1997(Hogers et al, , 1999. Groenendijk et al (2005) described changes in expression patterns of KLF2, endothelin-1 (ET-1), and endothelial nitric oxide synthase-3 (eNOS/NOS-3) already within 3 hr after clipping, suggestive of an increase in cardiac shear stress (Groenendijk et al, 2005(Groenendijk et al, , 2007.On a cellular level, Tgfb is a multipotent cytokine that plays pivotal roles in the regulation of proliferation, differentiation, migration, and survival of EC (Lebrin et al, 2005). After secretion and activation, Tgfb ligands bind their specific type I and type II serine/threonine kinase receptors.…”
mentioning
confidence: 99%